O-Acetylation of Plant Cell Wall Polysaccharides - Gille, Sascha; Pauly, Markus (Frontiers in Plant Science, 2012)
Plant cell walls are composed of structurally diverse polymers, many of which are O-acetylated. How plants O-acetylate wall polymers and what its function is remained elusive until recently, when two protein families were identified in the model plant Arabidopsis that are involved in the O-acetylation of wall polysaccharides – the reduced wall acetylation (RWA) and the trichome birefringence-like (TBL) proteins. This review discusses the role of these two protein families in polysaccharide O-acetylation and outlines the differences and similarities of polymer acetylation mechanisms in plants, fungi, bacteria and mammals. Members of the TBL protein family had been shown to impact pathogen resistance, freezing tolerance, and cellulose biosynthesis. The connection of TBLs to polysaccharide O-acetylation thus gives crucial leads into the biological function of wall polymer O-acetylation. From a biotechnological point understanding the O-acetylation mechanism is important as acetyl-substituents inhibit the enzymatic degradation of wall polymers and released acetate can be a potent inhibitor in microbial fermentations, thus impacting the economic viability of e.g. lignocellulosic based biofuel production.